Recital pieśni-humoru-parodii Karol Hanusz Marta Mirska. (Słupsk : [s.n.], 1947)
Afisz inf. o recitalu 14.08.1047 r.
Keywords: Życie artystyczne -- Polska -- Słupsk -- 1945-1970.; Słupsk (Polska) -- 1945-1970 -- druki ulotne